1991
DOI: 10.1203/00006450-199109000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Immunoreactive Endothelin-1 Concentration in Human Fetal Blood: Its Relation to Asphyxia

Abstract: ABSTRACT. To elucidate the effects of birth stress on immunoreactive endothelin-1 (irET-1) concentrations in fetal blood, we determined irET-1 levels in cord plasma in different modes of delivery associated with or without complications such as asphyxia. The irET-1 concentrations in both the umbilical artery and vein were significantly higher than those found in maternal venous blood at delivery, although there was no significant difference between preterm and full-term infants. When plasma irET-1 concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
4
19
3
Order By: Relevance
“…The results of the present study indicate that preterm infants have high plasma ET concentrations on the 1st postpartum day (16.25 ± 8.14 and 21.81 ± 5.87 pmol/1) com pared to the levels reported in the literature for healthy subjects [19][20][21], Other studies [13][14][15][16] have shown that plasma concentra tions of ET-1-like immunoreactivity in cord blood of full-term neonates was much higher than in maternal blood.The cause of elevated plasma ET concentrations in newborns is un known. Active transport of ETs across the pla centa has been excluded in previous studies 319 [14,16] as a cause of this increase due to the absence of umbilical arteriovenous difference of ET concentrations.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The results of the present study indicate that preterm infants have high plasma ET concentrations on the 1st postpartum day (16.25 ± 8.14 and 21.81 ± 5.87 pmol/1) com pared to the levels reported in the literature for healthy subjects [19][20][21], Other studies [13][14][15][16] have shown that plasma concentra tions of ET-1-like immunoreactivity in cord blood of full-term neonates was much higher than in maternal blood.The cause of elevated plasma ET concentrations in newborns is un known. Active transport of ETs across the pla centa has been excluded in previous studies 319 [14,16] as a cause of this increase due to the absence of umbilical arteriovenous difference of ET concentrations.…”
Section: Discussionsupporting
confidence: 65%
“…Active transport of ETs across the pla centa has been excluded in previous studies 319 [14,16] as a cause of this increase due to the absence of umbilical arteriovenous difference of ET concentrations. However, the placenta could be a possible source for synthesis and secretion of ET-1, because the peptide was first cloned from a placental cDNA library [22], Nevertheless, birth stress and especially asphyxia most likely trigger ET synthesis and secretion in the fetal circulation at birth [16]. It has been reported that hypoxia directly stimulates ET-1 release from rat mesenteric arteries in vitro [23] and that experimental asphyxia increases plasma ET-1 concentra tions in the pig [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports had demonstrated high umbilical cord blood levels of ET-1 which were even more pronounced in newborns with birth asphyxia [19,20] leading to a significant negative correlation between ADM levels and pH in cord blood [21]. These observations could indicate that birth stress may be an acute stimulus for the production of ADM and ET-1 in vascular endothelium.…”
Section: Discussionmentioning
confidence: 55%
“…ET-1, a 21-amino acid peptide, can be released from the endothelium by various stimuli including shear stress, stretch, pressure, hypoxia, thrombin, epinephrine, phorbol ester, transforming growth factor-ß and other pharmacological agents [3,[21][22][23][24]. Animal studies have shown that hypoxia [25][26][27][28] and vascular injury [29][30] can increase ET-1 level.…”
Section: Discussionmentioning
confidence: 99%